Effective use of the Bakri postpartum balloon for posthysterectomy pelvic floor hemorrhage - Kittipat Charoenkwan (2018)
After hysterectomy, massive pelvic floor hemorrhage sometimes occurs, especially in those who underwent complicated procedures. Conventional methods frequently fail to control this type of life-threatening bleeding. This report demonstrates the successful application of the large-volume Bakri balloon as a pelvic pressure pack for the control of intractable pelvic floor hemorrhage after hysterectomy in 3 consecutive cases. The Bakri balloon was introduced through the laparotomy incision and was passed inflation port first through a small posterior culdotomy to the vagina. The shaft of the balloon then was pulled through the vaginal canal. When proper tamponade position was achieved, the balloon was inflated gradually with sterile normal saline solution up to the minimal volume that effectively compressed against the pelvic floor and successfully controlled the hemorrhage. Continuous traction was used by the connection of the balloon shaft to a 1-L intravenous fluid bag that was hanging from the end of the bed. In all cases, the bleeding was controlled promptly when the balloons were filled up to 400-550 mL. The balloons were removed at bedside 24-30 hours after the operation. On follow-up examination, all patients recovered well without complication. From the author's experience, pelvic pressure packing with the Bakri balloon can be an immediate lifesaver. It is safe and readily applicable and provides a period of temporary hemostasis during which time volume replacement and coagulation defect correction can be obtained. The balloon pack can be removed vaginally without the need for reexploration. It is easy and fast to assemble, apply, and remove. In addition, the size of the balloon pack is adjustable easily to match the size of hemorrhagic areas by merely inflating or deflating the balloon. Furthermore, it is convenient to monitor continuing intraabdominal blood loss through the balloon's drainage port without the need for an additional drain. Further exploration on its use would be worthwhile.